2018
DOI: 10.1371/journal.pone.0202659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-point acupuncture (HT7) in the prevention of test anxiety: Results of a RCT

Abstract: BackgroundThe number of students using neuro enhancement to improve their performance and to prevent test anxiety is increasing. The acupuncture point Heart 7 (HT7) has been described as being prominent in reducing states of anxiety.MethodsWe conducted a randomized placebo-controlled, two-armed pilot trial to investigate the efficacy of a single-point acupuncture treatment at bilateral HT7 compared to sham laser acupuncture on test anxiety. Test anxiety was induced applying the standardised protocol of the Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For example, in Germany 13% of all first-year undergraduate students seek counseling services for test anxiety 3 . Anxiety in test situations has different facets, including affective (e.g., a nervous feeling of excitement), physiological (e.g., heart rate, sweating), motivational (e.g., avoidance tendencies) and cognitive components (e.g., concerns for failure) 4 . It has been shown that test anxiety weakens the ability to perform cognitively challenging tasks and reduces motivation, although test anxiety can also be beneficial for motivation, for example, when students try to avoid errors more rigorously 1 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Germany 13% of all first-year undergraduate students seek counseling services for test anxiety 3 . Anxiety in test situations has different facets, including affective (e.g., a nervous feeling of excitement), physiological (e.g., heart rate, sweating), motivational (e.g., avoidance tendencies) and cognitive components (e.g., concerns for failure) 4 . It has been shown that test anxiety weakens the ability to perform cognitively challenging tasks and reduces motivation, although test anxiety can also be beneficial for motivation, for example, when students try to avoid errors more rigorously 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that there was a reduction in stress hormones and heart rate compared to existing reference data. Changes in other parameters were not significant [59]. Both auricular acupuncture and placebo interventions reduced the exam anxiety in forty-four medical students of University Medicine of Greifswald, Germany.…”
Section: Cancermentioning
confidence: 68%
“…GB30 (at the junction of the lateral 1/3 and medial 2/3 of the greater trochanter with the sacral hiatus) and GB34 (in the depression anterior and distal to the head of the fibula) are combinations of acupoints that are utilized for the treatment of lumber neuropathic pain in the clinic (Cho et al, 2013; Ju et al, 2017). HT7 (radial to the flexor carpi ulnaris tendon on the palmar crease) and GV20 (on the vertex of the head) are combinations of acupoints frequently used for the treatment of cognitive and emotional impairments (Lee et al, 2012; Chen et al, 2016; Fleckenstein et al, 2018; Yu et al, 2018). The detailed locations of acupoints were shown in Figure 1A.…”
Section: Methodsmentioning
confidence: 99%